Artificial intelligence in patient education: a case study on peripheral artery disease - Chander, Shafak (International Journal of Research in Medical Sciences, 2025)
The Gemini chatbot is a conversational artificial intelligence (AI) system developed by google and launched in December 2023. It functions as a multimodal large language model (LLM). This means it’s not limited to understanding and generating texts; it can process and respond to various types of information, including images audios and videos. Users can interact with it by typing or speaking prompts.